KORELASI PENGETAHUAN IBU DAN UPAYA PROMOSI KESEHATAN TERHADAP PERILAKU PENCEGAHAN STUNTING - Kasim, Ahmad Muhammad; Kusumawardani, Emi; Noviasari, Damai; Handayani, Sekar; Soumokil, Octovina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Stunting in West Java Province is still a serious problem, with a high prevalence rate. One of the sub-districts in Bogor Regency that has a high stunting rate is Dramaga Sub-district in 2022, where the number of stunting cases reached 35 children. The purpose of the study was to determine the correlation between maternal knowledge and health promotion efforts on the incidence of stunting. This type of research is quantitative with a cross sectional design. The research was conducted in June 2023. The population is all families who have toddlers in Ciherang Village, Dramaga District, Bogor Regency. The sample amounted to 87 people. The sampling technique used Simple Random Sampling. The research instrument used a research questionnaire. Data analysis was conducted univariate and bivariate. The results showed that there was a relationship between knowledge (p value: 0.016) and health promotion efforts (p value: 0.008) with stunting prevention behavior in Ciherang Village, Dramaga District, Bogor Regency. It is recommended that Beneficiary Families of the Family Hope Program should be able to make efforts to prevent stunting by getting used to not doing activities in the river, meeting balanced nutritional needs for the family and routinely taking blood supplement tablets since adolescence and during the fertile period, because this can help prevent stunting in children.Keywords: Toddlers, Knowledge, Stunting.